Benin School Feeding : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents an assessment of school feeding policies and institutions that affect young children in Benin. The analysis is based on a World Bank tool developed as part of the systems approach for better education results (SABER) initiative that aims to systematically assess education systems against evidence based global standards and good practice to assist countries reform their education systems for proper learning for all. SABER school feeding collects, analyzes, and disseminates comprehensive information on school feeding policies around the world. The overall objective of the initiative is to help countries design effective policies to improve their education systems facilitate comparative policy analysis, identify key areas to focus investment, and assist in disseminating good practice.